РЕСУРСИ РЕЗИЛЬЄНТНОСТІ ОСІБ З ТРАВМАТИЧНИМ ДОСВІДОМ - Малімон, Людмила; Пархоменко, Вікторія (Psykholohichni perspektyvy = Psychological prospects, 2024)
Purpose. Theoretical study of resilience and the resources that determine the difference in its manifestation after critical situations, as well as empirical research on the mechanisms and resources that promote the development of resilience in people with traumatic experiences because of the war in Ukraine. Methods. Methods of theoretical analysis of scientific literature on the problem; methods of empirical research using a set of psychodiagnostic techniques; methods of mathematical statistics. Spearman's rank correlation coefficient was calculated for statistical data processing. Results. According to the results of theoretical analysis, the concept of "resilience" is considered as both a process and an outcome of successful adaptation to difficult life situations, especially through mental, emotional, and behavioral flexibility and adaptation to external and internal challenges. The empirical study revealed positive correlations of psychological resilience with resources (crisis coping strategies) "B – Belief & values" (r=0.591), “C – Cognition, thought” (r=0.540). A directly proportional correlations was also found between the overall impact of the event, the level of intrusion and avoidance with the crisis coping strategy "I – Imagination" (r=0.505; r=0.607; r=0.506), between the level of avoidance and the resource “S – Socialization” (r=0.632), between the level of intrusion and “C – Cognition, thought” (r=0.491). Conclusions. Individuals whose crisis coping strategies are based on faith (in God, in people, in miracles, or in themselves and their mission), belief systems, values and meanings, the activation of mental abilities, the ability to think logically and critically, assess situations, learn new ideas, plan, gather information, analyze problems, and solve them rationally, exhibit higher resilience indicators. Those who have higher level of impact of event and manifestations of specific PTSD symptoms more frequently use imagination, memories, and creativity to cope with crises. The level of avoidance positively correlates with the use of social ties, social support, and communication to cope with crises, and the level of intrusion positively correlates with the use of cognition and cognitive strategies. Мета. Теоретичне вивчення проблеми резильєнтності особистості й емпіричне дослідження ресурсів резильєнтності у людей з травматичним досвідом унаслідок воєнних дій в Україні. Методи. Методи теоретичного аналізу наукової літератури; емпіричного дослідження за допомогою комплексу психодіагностичних методик; методи математичної статистики (коефіцієнт кореляції Спірмена для виявлення взаємозв’язку досліджуваних показників). Результати. Розглянуто поняття резильєнтності як процесу і результату успішної адаптації особистості до складних життєвих ситуацій, особливо завдяки розумовій, емоційній та поведінковій гнучкості та пристосуванню до зовнішніх і внутрішніх викликів. За результатами емпіричного дослідження виявлено позитивні кореляційні взаємозв’язки психологічної стійкості (за шкалою CD-RISC-25) із ресурсами резильєнтності (способами подолання кризи) «B – Belief & values – віра, переконання, цінності, філософія життя» (r=0,591), «C – Cognition, thought – розум, пізнання, когнітивні стратегії» (r=0,540); позитивні зв’язки загального показника впливу травматичної події, прояву інтрузій та уникнення із способом подолання кризи «I – Imagination – уява, мрії, спогади, творчість» (r=0,505; r=0,607; r=0,506), а також проявом інтрузій та ресурсом «C – Cognition, thought – розум, пізнання, когнітивні стратегії» (r=0,491). Висновки. Особи, в яких спосіб подолання кризи базується на вірі (в Бога, в людей, в диво чи в самого/саму себе, у свою місію), системі переконань, цінностей та смислів, актуалізації ментальних здібностей, вмінні логічно та критично мислити, оцінювати ситуацію, пізнавати нові ідеї, планувати, навчатися, збирати інформацію, аналізувати проблеми та раціонально вирішувати їх, показники резильєнтності вищі. Особи, які мають вищі показники загального впливу травматичної події та проявів окремих симптомів ПТСР, частіше використовують уяву, спогади та творчість для подолання кризи;  особи, в яких домінують інтрузії як прояв травматичного досвіду, схильні використовувати пізнання та когнітивні стратегії подолання кризи.